(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study examines the principles of ‘ām and khāṣṣ in the Qur’an from the perspective of Imam Jalaluddin as-Suyuthi, as presented in his work Al-Itsqān fī ulūm al-Qur’ān. The concepts of ‘ām and khāṣṣ constitute a fundamental part of Qur’anic studies, as they are closely related to understanding the scope of lexical meanings and their legal implications. This research employs a library research method with a descriptive-analytical approach to Qur’anic verses and the opinions of muslim scholars. The findings show that Imam Jalaluddin as-Suyuthi classifies general expressions (lafz ‘ām) into several cetegories, namely ‘ām Al-Bāqī ‘alā ‘umūmihi, Al- ‘ām Al-Murādu bihi Al-Khuṣuṣi, Al- ‘ām Al-Makhṣūṣ. Furthermore, khāṣṣ is divided into khāṣṣ muttasil dan khāṣṣ munfasil, with various sources of specification, including the Qur’an, hadith, ijmā, Qiyās. A proper understanding of these principles underscores the importance of methodological precision in Qur’anic interpretation in order to avoid errors in generalizing meanings and in deriving legal rulings.